Migração seletiva de retorno e distribuição salarial: evidências para população migrante em São Paulo - Magalhães, Juliane do Carmo Duarte (2020)
The main objective of this dissertation was to analyze the effects of return migration on the wage distribution of interstate migrants residing in São Paulo. To recover the distribution of the total migrant population in the presence of selective return migration, data from the 2010 Demographic Census and an estimator method that takes into account the selection in unobservable were used. The findings of this study point to a negative selection in observables and non-observables in the outflow to the state of São Paulo. Bearing in mind that returned migrants have productive characteristics not observed better when compared to permanent migrants. Return migration worsens inequality outmigration of positively selected workers. The gap between migrants and natives, in turn, would be partially reduced if all migrants remained in the state.